Reforming regulation - Clark, Timothy B.; Kosters, Marvin H.; Miller, James Clifford; American Enterprise Institute for Public Policy Research (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1980)
This is a proceedings of a conference sponsored by the American Enterprise Institute for Public Policy Research and the National Journal.
lje 24/01/2019
Loans
Keywords: Independent regulatory commissions; Administrative law; Trade regulation